Lead-acid battery and manufacturing method for the same
Patent Information
- Application Number
- JP2023137832
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0010】 本開示の一側面によれば、歩留まりを維持もしくは向上しつつ、電気容量のさらなる向上が可能な鉛蓄電池及びその製造方法を提供できる。
Smart Images

Figure 2025032526000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a lead-acid battery and a method for manufacturing the same. [Background technology]
[0002] Lead-acid batteries have been widely used as secondary batteries for industrial or consumer use. For example, Patent Document 1 below discloses a lead-acid battery in which an active material is filled into a lattice plate having a frame and horizontal and vertical lattice frames that form a lattice inside the frame to form an electrode plate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-89511 A Summary of the Invention [Problem to be solved by the invention]
[0004] In lead-acid batteries, like other batteries, it is desirable to maintain or improve the yield while improving the design freedom.
[0005] An object of one aspect of the present disclosure is to provide a lead-acid battery and a manufacturing method thereof that enable improvement in design freedom while maintaining or improving yield. [Means for solving the problem]
[0006] In order to improve the electric capacity of a lead-acid battery, the ratio of the long side to the short side of the electrode plate (long-short ratio) can be increased to increase the degree of freedom in design. However, when the long-short ratio is increased, deformation such as warping is likely to occur during the manufacture of the electrode plate. In order to suppress the deformation, the electrode plate can be thickened. However, simply thickening the electrode plate reduces the degree of freedom in design of the lead-acid battery. After extensive research, the inventors have found a method that can achieve both suppression of deformation of the electrode plate during manufacture and improvement of the degree of freedom in design, even when the long-short ratio is increased, as described below. A lead-acid battery according to one aspect of the present disclosure is based on the above findings, and is a lead-acid battery including a negative electrode plate including a grid body of a lead alloy, in which the ratio of the long side to the short side of the negative electrode plate is 1.8 to 4.0, and the lead alloy contains 10 ppm or more of Bi. In such a lead-acid battery, the strength of the grid body is improved by Bi. Therefore, even when the ratio of the long side to the short side of the negative electrode plate is increased to the above range, it is possible to suppress deformation of the negative electrode plate during manufacture. Therefore, in the lead-acid battery according to one aspect of the present disclosure, it is possible to improve design freedom while maintaining or improving yield.
[0007] The lead alloy may be 30 ppm or more and 100 ppm or less, and the ratio of the long side to the short side of the negative electrode plate may be 2.5 or more. In this case, deformation of the negative electrode plate during production can be effectively suppressed.
[0008] The ratio of the long side to the short side of the negative electrode plate may be equal to or less than 3.0, which can effectively prevent deformation of the negative electrode plate during production.
[0009] A method for manufacturing a lead-acid battery according to another aspect of the present disclosure includes a first step of mixing a first lead raw material and a second lead raw material having different Bi contents to form a lead alloy, and a second step of forming a grid from the lead alloy, and in the first step, the ratio of the second lead raw material to the first lead raw material in the lead alloy is adjusted so that the Bi content in the grid is 10 ppm or more. In this method for manufacturing a lead-acid battery, the strength of the grid is improved by Bi. Therefore, even if the long-short ratio of the grid is increased, deformation of the plate during manufacturing due to insufficient strength of the grid can be suppressed. Therefore, by using the above manufacturing method, it is possible to improve the design freedom while maintaining or improving the yield. Effect of the Invention
[0010] According to one aspect of the present disclosure, it is possible to provide a lead-acid battery and a manufacturing method thereof that are capable of further improving the electrical capacity while maintaining or improving the yield. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is an exploded perspective view showing a lead-acid battery according to one embodiment. [Diagram 2] FIG. 2(a) is a plan view showing the grid of the negative electrode plate, and FIG. 2(b) is a side view showing the grid of the negative electrode plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment according to one aspect of the present disclosure will be described in detail with reference to the accompanying drawings. In the following description, the same elements or elements having the same functions will be denoted by the same reference numerals, and duplicated descriptions will be omitted.
[0013] <Lead acid battery> FIG. 1 is an exploded perspective view showing a lead-acid battery according to one embodiment. The lead-acid battery 1 shown in FIG. 1 is a battery used in, for example, automobiles, electric vehicles, power supply devices, etc. Examples of electric vehicles include electric forklifts and golf carts. Examples of power supply devices include UPS (Uninterruptible Power Supply), power supplies for disaster prevention (emergency) radio, and power supplies for telephones. The lead-acid battery 1 is, for example, a valve-regulated lead-acid battery. In a valve-regulated lead-acid battery, there is no free electrolyte flowing inside the battery. Therefore, there is an advantage that the electrolyte will not spill even if the battery is placed horizontally. In addition, the valve-regulated lead-acid battery can suppress the generation of hydrogen gas even if an electrolysis reaction of water occurs during charging. This has the effect of reducing oxygen gas generated by a chemical reaction on the surface of the negative electrode to water and returning it to the electrolyte.
[0014] 1, the lead-acid battery 1 includes a plurality of positive electrode plates 2 (positive electrodes), a plurality of negative electrode plates 3 (negative electrodes), a plurality of separators 4, a hollow battery case 5, and a lid 6 that seals the battery case 5. The lid 6 is provided with a control valve 7 for discharging excess gas to the outside of the battery case 5, a positive terminal 8 that connects the positive electrode plates 2 to the outside, and a negative terminal 9 that connects the negative electrode plates 3 to the outside.
[0015] In the battery case 5, the positive electrode plates 2 and the negative electrode plates 3 are arranged alternately. In addition, a separator 4 is arranged between the positive electrode plates 2 and the negative electrode plates 3. The electrode plate group consisting of the positive electrode plates 2, the negative electrode plates 3, and the separators 4 thus stacked is contained in the battery case 5.
[0016] The ears 2a of each positive electrode plate 2 are connected to each other via a strap 2b, so that the positive electrode plates 2 are electrically connected to each other. Similarly, the ears 3a of each negative electrode plate 3 are connected to each other via a strap 3b, so that the negative electrode plates 3 are electrically connected to each other. The strap 2b of the positive electrode plate 2 is provided with a positive electrode pole 2c for connecting the positive electrode plate 2 to a positive electrode terminal 8. Similarly, the strap 3b of the negative electrode plate 3 is provided with a negative electrode pole 3c for connecting the negative electrode plate 3 to a negative electrode terminal 9.
[0017] The positive electrode plate 2 includes a positive electrode grid and a positive electrode material filled between the grids of the positive electrode grid. The positive electrode grid is not particularly limited, but is formed of, for example, a lead alloy containing Pb, Ca, Sn, and Al. The lead alloy may further contain Bi, Ag, etc. The positive electrode grid is obtained, for example, by casting the lead alloy.
[0018] The positive electrode material contains, for example, a positive electrode active material (lead dioxide) and an additive. The positive electrode material is not particularly limited, but may be a paste-like positive electrode material obtained by mixing lead powder, red lead, dilute sulfuric acid, water, and an additive. The additive may be, for example, short reinforcing fibers (polypropylene fibers, PET (polyethylene terephthalate), acrylic fibers, etc.) added for the purpose of increasing the strength of the positive electrode material. The 10HR rated capacity of the positive electrode plate 2 may be, for example, 25 Ah per sheet.
[0019] The positive electrode plate 2 is obtained by filling the spaces between the lattices of the positive electrode grid with a paste-like positive electrode material, followed by an aging step and a drying step. In the aging step, the material is aged for 4 to 40 hours in an environment at a temperature of 75 to 85°C and a relative humidity of 95 to 98%, and then aged for 20 hours or more in an environment at a temperature of 50 to 65°C and a relative humidity of 50% or more. In the drying step, the material is dried for 20 to 40 hours in an environment at a temperature of 40 to 65°C, for example.
[0020] The negative electrode plate 3 includes a negative electrode grid and a negative electrode material filled between the grids of the negative electrode grid. A grid described later is used as the negative electrode grid. The negative electrode material contains, for example, a negative electrode active material (lead) and an additive. The negative electrode material is not particularly limited, but is, for example, a paste-like negative electrode material obtained by mixing lead powder with dilute sulfuric acid, water, and an additive. The additive may be barium sulfate (BaSO4) that functions as the nucleus of lead sulfate (PbSO4) generated during discharge, an organic compound such as lignin that suppresses the crystal growth of the negative electrode active material particles, a carbon material that imparts conductivity, a reinforcing short fiber, or the like. The reinforcing short fiber may be PET, acrylic fiber, or the like, as in the positive electrode plate.
[0021] The negative electrode plate 3 is obtained by filling the spaces between the lattices of the negative electrode grid with a paste-like negative electrode material, followed by an aging step and a drying step. In the aging step, the material is aged for about 24 hours in an environment with a temperature of 37 to 43°C and a relative humidity of 92 to 98%, and then aged for 16 hours or more in an environment with a temperature of 37 to 43°C and a relative humidity of 50% or more. In the drying step, the material is dried for 12 to 40 hours in an environment with a temperature of 35 to 45°C.
[0022] The separator 4 is an electrolyte retainer (retainer) that retains an electrolyte such as dilute sulfuric acid. The separator 4 may be in a plate shape as shown in FIG. 1, or in another embodiment, may be in a bag shape capable of wrapping a positive electrode plate. The separator 4 is not particularly limited as long as it holds an electrolyte and allows sulfate ions and hydrogen ions (protons) to pass therethrough while preventing electrical contact between the positive electrode plate 2 and the negative electrode plate 3. The separator 4 is preferably an AGM (Absorbed Glass Mat) made by papermaking fine glass fiber (cotton). The thickness of each separator (retainer) 4 is set arbitrarily, but may be 1 to 3 mm for a backup lead-acid battery, for example. When dilute sulfuric acid is used as the electrolyte, the specific gravity of the dilute sulfuric acid (converted at 20° C.) is, for example, 1.25 to 1.35.
[0023] The battery case 5 is not particularly limited as long as it can accommodate an electrode plate group consisting of the positive electrode plate 2, the negative electrode plate 3, and the separator 4 and has resistance to an electrolyte such as dilute sulfuric acid. The battery case 5 is made of PP (polypropylene), PE (polyethylene), ABS resin, or the like.
[0024] In one embodiment, the inside of the battery case may be divided into a plurality of cell chambers. In this case, a plate group is housed in each cell chamber. Then, a plate group housed in one cell chamber and a plate group housed in an adjacent cell chamber are connected to each other so that the straps of opposite polarity are connected to each other, thereby forming a lead-acid battery having a predetermined rated voltage or rated capacity.
[0025] The lid 6 is formed, for example, from the same material as the battery case 5 so as to be able to seal the battery case 5. The lid 6 is attached to the battery case 5 by, for example, heat fusion or adhesion using an adhesive.
[0026] (Negative plate grid) Fig. 2(a) is a plan view showing the grid of the negative electrode plate. Fig. 2(b) is a side view showing the grid of the negative electrode plate. As shown in Figs. 2(a) and (b), the grid 11 includes a grid portion 12 formed in a grid shape and a lug portion 13 provided on a part of the outer edge of the grid portion 12.
[0027] The lattice section 12 includes a frame forming a substantially rectangular outer shell, and inner frames arranged in a lattice pattern inside the outer shell. The frame includes a pair of substantially parallel vertical frame frames 14 extending in the longitudinal (vertical) direction, and a pair of substantially parallel horizontal frame frames 15 extending in the transverse (horizontal) direction. The inner frame includes a plurality of substantially parallel vertical inner frame frames 16 extending in the longitudinal (vertical) direction, and a plurality of substantially parallel horizontal inner frame frames 17 extending in the transverse (horizontal) direction. The ears 13 extend in the longitudinal direction from a portion of the horizontal frame frames 15 to the outside of the outer shell, and are shaped like a substantially rectangular plate.
[0028] In the lattice portion 12, the length L1 of the vertical frame 14 corresponds to the lattice height of the lattice body 11, and the length L2 of the horizontal frame 15 corresponds to the lattice width of the lattice body 11. The lengths L1 and L2 can be appropriately adjusted depending on the application and performance of the lead-acid battery. In one embodiment, the length L1 is greater than the length L2. Therefore, the length L1 can also be called the long side of the negative electrode plate 3, and the length L2 can also be called the short side of the negative electrode plate 3. From the viewpoint of improving the design freedom of the negative electrode plate 3, the ratio of the long side to the short side of the negative electrode plate 3 (long-short ratio) is 1.8 or more. In this case, it is particularly easy to manufacture a vertically long lead-acid battery. From the viewpoint of suppressing the occurrence of deformation such as warping during the manufacture of the negative electrode plate 3, the long-short ratio of the negative electrode plate 3 is 4.0 or less. The length-to-short ratio of the negative electrode plate 3 may be 2.0 or more, 2.2 or more, 2.5 or more, 3.5 or less, 3.0 or less, or 2.9 or less.
[0029] From the viewpoint of suppressing the occurrence of deformation such as warping during the manufacture of the negative electrode plate 3, the thickness T of the vertical frame 14 is 1.6 mm or more. From the viewpoint of the electrical performance of the negative electrode plate 3, the thickness T of the vertical frame 14 is 2.9 mm or less. The thickness T of the vertical frame 14 may be 1.8 mm or more, 2.0 mm or more, 2.2 mm or more, 2.8 mm or less, 2.6 mm or less, or 2.5 mm or less. In one embodiment, the thickness T of the vertical frame 14 is substantially the same as the thickness of the horizontal frame 15, the thickness of the vertical inner frame 16, and the thickness of the horizontal inner frame 17. Therefore, in one embodiment, the thickness T of the vertical frame 14 is considered to be the thickness of the grid body 11 (grid thickness).
[0030] The grid 11 is formed of a cast grid of a lead alloy mainly composed of Pb (lead). The lead alloy in the grid 11 is an alloy containing at least Pb and Bi (bismuth). In one embodiment, the lead alloy may contain Ca (calcium), Sn (tin), and other unavoidable impurities in addition to Pb and Bi. In other words, the grid 11 is a cast grid of a lead alloy containing Pb, Bi, Ca, and Sn. The lead alloy before casting may contain other elements in addition to Pb, Bi, Ca, and Sn. The other elements are, for example, a part of the unavoidable impurities or elements discharged during casting of the lead alloy and contained in trace amounts in the grid 11. The trace amount is, for example, less than 1 / 10 of the Bi content in the lead alloy. In the following, the "lead alloy" corresponds to the lead alloy forming the grid 11 unless it is specified as the "lead alloy before casting". Examples of the unavoidable impurities include As, Cu, Fe, Mg, Ni, Zn, etc. The content of the unavoidable impurities (the total amount of the above components) is, for example, 200 ppm or less based on the total mass of the lead alloy (hereinafter simply referred to as "total mass basis").
[0031] The Pb content in the lead alloy is, for example, 97 mass % or more, 98 mass % or more, or 99 mass % or more based on the total mass. The Pb content may be 99.9 mass % or less.
[0032] By including Bi in the lead alloy, the strength of the grid 11 is improved, and thus deformation such as warping during the manufacture of the negative electrode plate 3 is less likely to occur. From this viewpoint, in one embodiment, the lead alloy includes 10 ppm or more of Bi based on the total mass. On the other hand, if the lead alloy includes excessive Bi, it becomes difficult to maintain the hydrogen generation potential of the negative electrode plate 3. In addition, the impurity concentration of the lead alloy itself increases, and the electrical performance of the negative electrode plate 3 tends to deteriorate. From these viewpoints, in one embodiment, the lead alloy includes 100 ppm or less of Bi based on the total mass of the alloy. The lead alloy may include 20 ppm or more of Bi, 30 ppm or more of Bi, 40 ppm or more of Bi, 80 ppm or less of Bi, 60 ppm or less of Bi, or 50 ppm or less of Bi.
[0033] The Ca content in the lead alloy is, for example, 700 ppm or more and 1500 ppm or less based on the total mass. From the viewpoint of the strength of the grid 11, the Ca content may be 800 ppm or more or 900 ppm or more based on the total mass. From the viewpoint of suppressing the deterioration of battery performance due to recrystallization at high temperatures and deformation of the grid 11, high temperature durability, etc., the Ca content may be 1200 ppm or less or 1000 ppm or less based on the total mass. The Ca content may be 700 to 1200 ppm, 700 to 1000 ppm, 800 to 1500 ppm, 800 to 1200 ppm, 800 to 1000 ppm, 900 to 1500 ppm, 900 to 1200 ppm, or 900 to 1000 ppm based on the total mass.
[0034] The Sn content in the lead alloy is, for example, 1000 ppm or more and 20000 ppm or less on a total mass basis. From the viewpoint of corrosion resistance, the Sn content may be 5000 ppm or more or 10000 ppm or more on a total mass basis. From the viewpoint of the strength of the lattice body, maintenance of hydrogen generation potential, etc., the Sn content may be 18000 ppm or less or 15000 ppm or less on a total mass basis. The Sn content may be 1000 to 18000 ppm, 1000 to 15000 ppm, 5000 to 20000 ppm, 5000 to 18000 ppm, 5000 to 15000 ppm, 10000 to 20000 ppm, 10000 to 18000 ppm, or 10000 to 15000 ppm on a total mass basis.
[0035] When the lead alloy contains Ca and Sn, the lead alloy may further contain Ag and / or Al, in which case Ca and Sn are more likely to be present in the lead alloy.
[0036] The content of Ag in the lead alloy may be, for example, 1 ppm or more, 2 ppm or more, 4 ppm or more, or 5 ppm or more based on the total mass from the viewpoint of creep properties of the lattice at high temperatures. The content of Ag may be, for example, 20 ppm or less, 10 ppm or less, or 6 ppm or less based on the total mass from the viewpoint of maintaining hydrogen generation potential. The content of Ag may be, for example, 1 to 20 ppm, 1 to 10 ppm, 1 to 6 ppm, 2 to 20 ppm, 2 to 10 ppm, 2 to 6 ppm, 4 to 20 ppm, 4 to 10 ppm, or 4 to 6 ppm based on the total mass.
[0037] The content of Al in the lead alloy may be, for example, 20 ppm or more, 50 ppm or more, or 80 ppm or more based on the total mass from the viewpoint of preventing generation of oxidizing gas during casting. The content of Al may be, for example, 200 ppm or less, 170 ppm or less, or 150 ppm or less based on the total mass from the viewpoint of homogenizing the alloy structure. The content of Al may be, for example, 20 to 200 ppm, 20 to 170 ppm, 20 to 150 ppm, 50 to 200 ppm, 50 to 170 ppm, 50 to 150 ppm, 80 to 200 ppm, 80 to 170 ppm, or 80 to 150 ppm based on the total mass.
[0038] Next, an example of a manufacturing method of the lead acid battery 1 according to an embodiment will be described. First, an example of a manufacturing method of the grid of the negative electrode plate will be described in detail. This example includes a first step of mixing a first lead raw material and a second lead raw material having different Bi contents to prepare a lead alloy, and a second step of forming a grid from the lead alloy. In the first step, the ratio of the second lead raw material to the first lead raw material in the lead alloy is adjusted so that the Bi content in the grid is 10 ppm or more.
[0039] In the first step, the first lead raw material is first put into a kettle and melted (step A). In one example, one or more first lead alloy ingots, which are the first lead raw material, are put into the kettle. Then, the second lead raw material is put into the kettle and melted (step B). In one example, one or more second lead alloy ingots, which are the second lead raw material, are put into the kettle containing the molten first lead raw material. The step A may be performed after the step B. Then, the first lead raw material and the second lead raw material are appropriately put into the kettle until a predetermined amount of ingots are put into the kettle, and a lead alloy (molten lead alloy) is generated to be melted in the kettle (step C). Oxidized scum floats on the surface of the molten lead alloy. The oxidized scum may or may not be removed.
[0040] Each of the first lead alloy ingot and the second lead alloy ingot is an alloy mainly composed of lead. The first lead alloy ingot is, for example, a refined lead ingot made from galena (PbS) or the like. The Bi content of the first lead alloy ingot is, for example, 0 ppm or more and 10 ppm or less. That is, the first lead alloy ingot may not contain Bi. By making the Bi content of the first lead alloy ingot 10 ppm or less, it is possible to prevent the Bi content of the lattice body formed in the second step from becoming excessive. The second lead alloy ingot is, for example, a recycled lead ingot made from lead scrap or the like. The raw material of the second lead alloy ingot may contain galena. The Bi content of the second lead alloy ingot is higher than the Bi content of the first lead alloy ingot, for example, more than 10 ppm and 100 ppm or less. In this case, the Bi content of the lattice body formed in the second step is stably 10 ppm or more and is unlikely to become excessive. In particular, even if the second lead alloy ingot is excessively charged into the kettle for some reason, the Bi content of the grid body is unlikely to be excessive. The Bi content of the second lead alloy ingot may be 15 ppm or more, 20 ppm or more, 25 ppm or more, 30 ppm or more, 40 ppm or more, 90 ppm or less, 80 ppm or less, 70 ppm or less, 60 ppm or less, or 50 ppm or less. The dimensions of the first lead alloy ingot and the second lead alloy ingot are not particularly limited. In one example, the dimensions of the first lead alloy ingot are substantially equal to the dimensions of the second lead alloy ingot.
[0041] The first lead alloy ingot and the second lead alloy ingot each contain Ca and Sn. The Ca content and the Sn content in each ingot are each adjusted in advance. This makes it difficult for the contents of elements other than Pb and Bi in the lattice body to deviate from the intended range. The first lead alloy ingot and the second lead alloy ingot each may further contain at least one of Ag and Al. In this case, the Ag content and the Al content in each ingot are also adjusted in advance. When the first lead alloy ingot and the second lead alloy ingot contain Ag, the Ag content of the first lead alloy ingot is, for example, 5 ppm or less, and the Ag content of the second lead alloy ingot is, for example, more than 5 ppm and 20 ppm or less. In this case, the Ag content of the lattice body formed in the second process is likely to be 5 ppm or more and is unlikely to be excessive. The Ag content of the second lead alloy ingot may be 6 ppm or more, 7 ppm or more, 15 ppm or less, 12 ppm or less, 10 ppm or less, or 9 ppm or less.
[0042] In one example, in the step C, the first lead raw material and the second lead raw material are appropriately charged so that the first lead raw material:second lead raw material=1:1 (mass ratio). In this case, the mass of the first lead raw material charged and the mass of the second lead raw material charged can be appropriately adjusted. In the step C, for example, the ratio of the second lead raw material to the first lead raw material in the molten metal can be appropriately adjusted depending on the shape of the lattice body produced in the second step (particularly, the thickness of the lattice body). That is, the "first lead raw material:second lead raw material (mass ratio)" of the molten metal is not limited to 1:1. For example, the content of the first lead raw material in the molten metal may be more than 0 and may be 90% or less. In this case, the melting of the first lead raw material and the second lead raw material in the kettle becomes more uniform, and the Bi content of the lattice body formed in the second step is more likely to be stabilized. In addition, the step of appropriately charging the first lead raw material and the second lead raw material into the kettle becomes easier to manage.
[0043] In the above step C, if there is a problem in the charging of at least one of the first lead raw material and the second lead raw material, the Bi content in the lattice body formed from the molten metal may deviate from the expected value. From the viewpoint of suppressing the deviation and homogenizing the composition of the molten metal, the first lead raw material and the second lead raw material may be charged alternately into the kettle in the above step C.
[0044] In the second step, the grid is formed from the molten lead alloy. In one example, the molten lead alloy is poured from a kettle into a casting device, and the grid is cast by a book mold method.
[0045] Next, an unformed negative electrode plate is formed from the formed grid. In one example, a paste-like negative electrode active material is filled into the grid, and then the negative electrode active material is aged and dried to form an unformed electrode plate. Next, a plate group including the negative electrode plate, an unformed positive electrode plate, and a separator is accommodated in a battery case. In this way, an unformed lead-acid battery is manufactured. Then, each positive electrode plate and each negative electrode plate are subjected to battery case formation by placing an electrolyte (dilute sulfuric acid) in the battery case. In one example, battery case formation is performed by passing a direct current through the unformed lead-acid battery containing the electrolyte. Then, after inspection, the lead-acid battery is manufactured.
[0046] The lead-acid battery 1 obtained by the manufacturing method according to the embodiment described above includes a negative electrode plate 3 including a grid 11 that is a cast grid of a lead alloy, and the lead alloy forming the grid 11 contains 10 ppm or more of Bi. In such a lead-acid battery 1, the strength of the grid 11 is improved by Bi. Therefore, even if the length-to-short ratio of the negative electrode plate 3 is increased to a range of 1.8 to 4.0, for example, the occurrence of warping of the negative electrode plate 3 during manufacturing can be suppressed. Therefore, the use of the lead-acid battery 1 makes it possible to improve design freedom while maintaining or improving the yield.
[0047] Here, the reason why the strength of the lattice body 11 is improved by including 10 ppm or more of Bi in the lead alloy forming the lattice body 11 is presumably as described below. That is, first, generally, metals are composed of many crystal grains with different atomic arrangement directions. Here, the disturbance of the atomic arrangement direction affects the properties of the metal material. It is also known that the additive elements and impurity elements of the alloy tend to become crystal nuclei or to gather near the boundaries between crystal grains (grain boundaries). The lattice body 11 formed from the lead alloy in one embodiment also has grain boundaries, and corrosion progresses along the grain boundaries (grain boundary corrosion). In this case, the bonds between the crystal grains become weak, and the lattice body 11 becomes easily deformed due to the volume expansion caused by corrosion. Here, the lattice body 11 according to one embodiment contains 10 ppm or more of Bi in addition to Pb. As a result, the crystal grains in the lattice body 11 are made fine, and the mesh structure of the grain boundaries increases. As a result, the bonding of the crystal grains is improved. Therefore, when the lead alloy contains Bi, the mechanical strength of the grid 11 is improved and deformation is reduced.
[0048] In one embodiment, the lead alloy may be 30 ppm or more and 100 ppm or less, and the ratio of the long side to the short side of the negative electrode plate 3 may be 2.5 or more. In this case, deformation of the negative electrode plate 3 during manufacturing can be effectively suppressed.
[0049] In one embodiment, the ratio of the long side to the short side of the negative electrode plate 3 may be equal to or less than 3.0. In this case, deformation of the negative electrode plate 3 during manufacturing can be effectively suppressed.
[0050] The lead-acid battery and the manufacturing method thereof according to one aspect of the present disclosure are not limited to the above embodiment. For example, in the above embodiment, the positive electrode plate has a grid body, but is not limited to this. For example, the positive electrode plate may have a clad electrode. In this case, the positive electrode plate has a core metal, a clad tube (a tube for holding active material) that covers the core metal, and a positive electrode material filled in the clad tube.
[0051] In the above embodiment, the first lead raw material and the second lead raw material are used in the first step, but this is not limited thereto. For example, in the above first step, the lead alloy may be formed using only a single lead raw material having a Bi content of more than 10 ppm. This makes the Bi content of the lead alloy forming the grid body 10 ppm or more. EXAMPLES
[0052] Hereinafter, one aspect of the present disclosure will be described more specifically based on examples, but the present disclosure is not limited to the following examples.
[0053] Example 1 <Negative electrode grid> A grid body having the grid thickness, grid height, and grid width shown in Table 1 below was cast using the book mold method, and hardened for 16 hours in a hardening furnace at 80° C. The Bi content of the lead alloy after casting was measured by matrix matching-ICP atomic emission spectrometry using a Thermo Fisher Scientific iCAP6300.
[0054] <Preparation of paste-like negative electrode material> 900 kg of lead powder, the main component of which is lead monoxide, 2.7 kg of PET fiber (fineness: 2.0D (denier), fiber length: 3.0 mm), 4.5 kg of barium sulfate, and 1.8 kg of lignin were mixed, water was added, and then 100 kg of dilute sulfuric acid was added and kneaded to produce a paste-like negative electrode material. The amount of water added was adjusted to ensure that the paste-like negative electrode material had a nearly constant hardness, taking into account the filling ability of the paste-like negative electrode material into the lattice body.
[0055] <Preparation of negative electrode plate> After filling the negative electrode grid prepared by the above method with the paste-type negative electrode material, the negative electrode grid was dried for 20 seconds in a furnace adjusted to 130°C as primary drying. Then, the negative electrode grid was aged and dried under the following conditions to prepare an unformed paste-type negative electrode plate. (Aging (primary storage)) Ambient temperature 35-55℃ for 8 hours (Aging (secondary storage)) Atmosphere temperature 65-85℃ for 12 hours or more
[0056] (Examples 2 to 6) A negative electrode plate was produced in the same manner as in Example 1, except that a grid having the Bi content shown in Table 1 below was cast.
[0057] Example 7 A negative electrode plate was produced in the same manner as in Example 1, except that a grid body having a grid height shown in Table 1 below was cast.
[0058] Comparative Example 1 A negative electrode plate was produced in the same manner as in Example 1, except that a grid having the Bi content shown in Table 1 below was cast.
[0059] <Degree of plate deformation during manufacturing> When the thickness of the grid filled with the paste-like negative electrode material and not aged or dried is X, and the thickness of the grid in the unformed paste-type negative electrode plate is Y, the calculation result of "(100 x Y / X) - 100" was taken as the degree of deformation (%) of the electrode plate during manufacture. The evaluation results of the degree of deformation of the electrode plate during manufacture were judged according to A to D shown below. The evaluation results of the degree of deformation of the electrode plate during manufacture in each Example and Comparative Example 1 are shown in Table 1 below. A: The degree of deformation of the plate during manufacturing is 10% or less B: The degree of deformation of the electrode plate during manufacturing is greater than 10% and less than 20%. C: The degree of deformation of the electrode plate during manufacturing is greater than 20%.
[0060] The thickness of the grid was measured according to the following procedure. First, the grid was placed flat and fixed on a horizontal surface. Then, the thickness of one end of the grid in the longitudinal direction and the thickness of the other end of the grid in the longitudinal direction were both measured using a thickness measuring device (ABS digital indicator ID-CX "IID-C112X" manufactured by Mitutoyo Corporation). The larger of the thickness of the one end and the thickness of the other end was taken as the thickness of the grid.
[0061] [Table 1] [Explanation of symbols]
[0062] 1...lead-acid battery, 2...positive electrode plate, 3...negative electrode plate, 4...separator, 5...cell case, 6...lid, 7...control valve, 8...positive electrode terminal, 9...negative electrode terminal, 11...grid, 12...grid portion, 13...ear portion, 14...vertical frame bone, 15...horizontal frame bone, 16...vertical inner bone, 17...horizontal inner bone.
Claims
1. A lead-acid battery having a negative plate including a lead alloy grid, The ratio of the long side to the short side of the negative electrode plate is 1.8 to 4.0, The lead alloy contains 10 ppm or more of Bi. Lead acid battery.
2. The lead alloy has a content of 30 ppm or more and 100 ppm or less, 2. The lead-acid battery according to claim 1, wherein the ratio of the long side to the short side of the negative plate is 2.5 or more.
3. 3. The lead-acid battery according to claim 1, wherein the ratio of the long side to the short side of the negative electrode plate is 3.0 or less.
4. A first step of mixing a first lead raw material and a second lead raw material having different Bi contents to form a lead alloy; and a second step of forming a grid from the lead alloy. In the first step, a ratio of the second lead raw material to the first lead raw material in the lead alloy is adjusted so that the content of Bi in the lattice body is 10 ppm or more. How lead-acid batteries are manufactured.
Citation Information
Patent Citations
Lead storage battery
JP2012089511A